2004
DOI: 10.1001/archotol.130.6.764
|View full text |Cite
|
Sign up to set email alerts
|

Disability in Patients With Head and Neck Cancer

Abstract: Background: Patients with head and neck cancer often experience debilitating speech, eating, and respiratory problems as well as the psychological effects of loss of function and change in body image. These patients often become unemployed as a result of their disease process, which adds financial burden to their already stressful lives. Yet the specific factors associated with unemployment have not been systematically studied.Methods: This multisite study used survey and chart data to determine the predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 27 publications
2
117
1
5
Order By: Relevance
“…3 Compared with patients with other types of cancer, those with head and neck cancer (HNC) have the third highest rate of discontinuing work because of their illness. 9 Prior studies [11][12][13][14] have reported that 28% to 52% of patients with HNC who were employed at the time of their diagnosis were disabled by their illness. With an increase in the survival of many patients with HNC over the past 30 years and an increase in the age at which retirement is anticipated, the importance of returning to work becomes a substantial concern for this group of patients who have previously been presumed to contribute relatively little to the work force.…”
Section: Resultsmentioning
confidence: 99%
“…3 Compared with patients with other types of cancer, those with head and neck cancer (HNC) have the third highest rate of discontinuing work because of their illness. 9 Prior studies [11][12][13][14] have reported that 28% to 52% of patients with HNC who were employed at the time of their diagnosis were disabled by their illness. With an increase in the survival of many patients with HNC over the past 30 years and an increase in the age at which retirement is anticipated, the importance of returning to work becomes a substantial concern for this group of patients who have previously been presumed to contribute relatively little to the work force.…”
Section: Resultsmentioning
confidence: 99%
“…The exposure of the salivary glands to high doses of radiation during radiotherapy results in salivary hypofunction, which may persist during the rest of the life of the patient leading to irreversible and distressing oral complaints. These consequences of treatment have a negative impact on the quality of life (1). Protection of the salivary glands against radiation damage is of great importance.…”
Section: Apoptosis and Expression Of Aqp5 And Tgf-β In The Irradiatedmentioning
confidence: 99%
“…Nearly one out of five cancer survivors reported cancer-related limitations in ability to work when interviewed 1-5 years following their diagnosis in one of the largest cross-sectional studies to date [23]. Work-related outcomes are significantly worse for cancers of the central nervous system, hematologic cancers [23], and cancer of the head and neck [24]. Other investigators point to the vulnerability of cancer survivors with jobs involving manual labor [25].…”
Section: Introductionmentioning
confidence: 99%